(untitled) (Tumou Tou: Jurnal Pengabdian Masyarakat, 2025)
Talawaan Village in North Minahasa Regency holds great potential for tourism development, particularly through its natural attraction, Tunan Waterfall. However, this potential has not been fully realized due to limited infrastructure and a lack of community capacity in sustainable tourism management. This community service program aimed to strengthen the knowledge and capabilities of local stakeholders, especially members of the Tourism Awareness Group (POKDARWIS), by promoting sustainable and inclusive tourism principles. The activities included socialization sessions, field observations, and participatory group discussions involving academics, students, and community members. Results showed increased understanding of sustainable tourism concepts, identification of key issues in the destination’s management, and the formulation of strategic recommendations. These include environmental conservation, active community involvement, development of local micro-enterprises, and institutional strengthening of POKDARWIS. The program also facilitated collaboration between the university and the local community, providing a platform for experiential learning and co-creation of solutions. In conclusion, sustainable tourism can be developed effectively at the village level through participatory approaches. Future programs should focus on capacity building in destination management, digital marketing, and local policy formulation to support inclusive economic growth and long-term sustainability.